Photo-Anthropometric Study of Inferior wall and Inferior orbital fissure of Fully Ossified Dry Human Orbital Cavities (Bangladesh Journal of Anatomy, 2017)
Background: Orbital morphometry is important to provide useful baseline data for ophthalmologist, anthropologist, otolaryngologist, radiologist, maxillo-facial surgeon, reconstructive cosmetic surgeon and forensic medicine expert. The existing data suggest that the location of various foramina in the orbit vary in different ancestral population. An understanding of orbital disease demands a clear concept of normal orbital anatomy. Safe and effective orbital surgery requires an extensive knowledge of the anatomy of the bony orbit and the morphometric relationship that exist within it. Materials and Methods: This cross sectional analytical study was performed on 200 (Two hundred) fully ossified dry orbital cavities of 100 human skulls collected from Department of Anatomy of different Medical Colleges of Dhaka city. Variation between different foramina in the walls of both orbital cavity at different landmarks were recorded in millimeter by photographic methods (Adobe photoshop version 10). Paired students ‘t’ test was done for statistical analysis of the result. Results: In the present study, no significant difference in the mean from infraorbital foramen to the closest margin of the inferior orbital fissure was observed between right and left orbital cavity (P>0.05). No significant difference in the mean from infraorbital foramen to the inferior border of the optic canal was observed between right and left orbital cavity (P>0.05). No significant difference (P>0.05) was observed in the mean length of posteromedial segment and middle segment between right and left inferior orbital fissure .Significant difference (P< 0.05) was found between the right and left inferior orbital fissure when compared the mean length of anteriolateral segment of inferior orbital fissure. Conclusions: There was significant difference in the measurement of distances from the length of anterolateral segment of right and left inferior orbital fissure. Other parameters showed no significant difference between right and left orbital cavities.Bangladesh Journal of Anatomy July 2017, Vol. 15, No. 1, pp. 9-14